1971
DOI: 10.1111/j.1365-2427.1971.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

The autecology of the chub, Squalius cephalus (L.), of the River Lugg and the Afon Llynfi

Abstract: Summary (1) Analysis of data from samples of chub taken at monthly intervals from two tributaries of the Herefordshire Wye revealed an annual cycle of scale growth with the formation ofa check during May or June. The frequency distributions of ages deter‐mined from scale checks and the length‐frequency distributions showed close simi‐larities. It was concluded that age determinations based on an examination of the scales were valid, provided care was taken in the identification ofthe first scale cheek. The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…With the Cyprinidae, it is difficult to estimate accurately the age of fish older than ten years, since erosion on the scales can be extensive and may mask certain annuli (Philippart 1972). Various authors have shown that female chub often have a faster growth rate than males of VI -VU years old (Cragg Hine & Jones 1969, Hellawell 1971, Mann 1976. During the present study, the specimens were released into the water after taking of scales, and therefore, their sex could not be determined.…”
Section: Sampling Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…With the Cyprinidae, it is difficult to estimate accurately the age of fish older than ten years, since erosion on the scales can be extensive and may mask certain annuli (Philippart 1972). Various authors have shown that female chub often have a faster growth rate than males of VI -VU years old (Cragg Hine & Jones 1969, Hellawell 1971, Mann 1976. During the present study, the specimens were released into the water after taking of scales, and therefore, their sex could not be determined.…”
Section: Sampling Methodsmentioning
confidence: 64%
“…The highest growth rate is found in stations 4D and 6V. In stations ID and 3D, growth is very similar, at least up to eight years, and may be compared with those on the English river Lugg (Hellawell 1971). At station 2D, the values are lower and similar to those reported by Libowarsky (1956) for the Suratka (Czechoslovakia), a river that has been disturbed by the construction of a hydroelectric dam and by Philippart (1972) for the Belgian Berwine, a severely polluted river.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several studies have demonstrated that temperature controls many biochemical processes of metabolic rate (Gillooly et al, 2001;Brown et al, 2004) and that a warmed temperature leads to an increase in basal and active metabolic rate as well as rates at which energy reserves are used by ectothermic organisms (Kassahn et al, 2009). Increases in the rate of physiological processes enable to raise fish activity among which locomotor (Lo´pez-Olmeda and Sa´nchez-Va´zquez, 2011) and foraging (Hathaway, 1927;Hellawell, 1971) activities.…”
Section: Discussionmentioning
confidence: 99%
“…B. barbatula buries in sediment for refuge and forages by sucking in large amounts of sediment, extracting a wide variety of small benthic invertebrates and plants, and releasing the sediment (Keith et al, 2011). P. toxostoma feeds mainly by grazing on benthic algae, diatoms and invertebrates (Chappaz et al, 1989;Keith et al, 2011), whereas S. cephalus is an opportunistic feeder eating both pelagic and benthic material (Hellawell, 1971;Keith et al, 2011). Both P. toxostoma and S. cephalus are also able to displace sediments when moving close to the streambed (see Statzner and Sagnes, 2008 for other cyprinid species; personal observation).…”
Section: Fish Speciesmentioning
confidence: 99%